Kajian Ekologi Hindu Dalam Bingkai Teologi Lokal Bali Sebagai Landasan Etika Konservasi Lingkungan - Hari Harsananda; Ida Bagus Putu Adnyana (Jurnal Penelitian Agama Hindu, 2026)
The accelerating degradation of global ecosystems necessitates a paradigm shift in environmental conservation efforts, transcending purely materialistic frameworks. This study aims to construct a theo-ecological framework grounded in Balinese local theology to serve as a philosophical foundation for sustainable nature preservation. Employing a qualitative methodology with a document study approach and in-depth textual analysis, this research examines Tutur Gong Besi, Brhad-aranyaka Upanisad, and Chandogya Upanisad. The findings reveal that Balinese local theology conceptualizes nature as an immanent manifestation of the Divine (Sarvam khalvidam Brahman). Within the text of Tutur Gong Besi, three integrated ecological dimensions are identified: landscape ecology (the sacralization of headwater-downstream zones), agrarian ecology (the sanctification of agricultural spaces and rice fields), and elemental ecology (the Divine permeating the Panca Maha Bhuta). Furthermore, the analysis demonstrates that traditional local wisdom concepts—such as Rwa Bhineda, Tri Mandala, Tri Hita Karana, Panca Maha Bhuta, and Sad Kerthi—do not operate in isolation; rather, they synergize to form a progressive hierarchy that constructs a solid ecocentric ethical framework for ecological interactions. This study concludes that Balinese local theology systematically provides a comprehensive Hindu ecological model that transforms conservation from mere technical-secular regulation into an absolute spiritual obligation. This theo-ecological framework proves effective and highly applicable for translation into environmental governance systems, modern public policies, and the strengthening of customary laws (hukum adat) to ensure long-term harmonious relations between the Divine, humanity, and the global environment.